Noncontact Optical Fiber Sensor for Measuring the Refractive Index of Liquids - Selvas Aguilar, Romeo; Castillo Guzmán, Arturo Alberto; Cortez González, Luis Carlos; Toral Acosta, Daniel; Martínez Ríos, Alejandro; Anzueto Sánchez, Gilberto; Durán Ramírez, Víctor M.; Arroyo Rivera, S. (2016)
A noncontact optical fiber sensor for measuring the refractive index of transparent liquids is proposed. It operates by calculating the path of a focused laser beam at 635 nm that travels across the boundaries of a liquid sample. The optical power Fresnel reflections are detected and, subsequently, the refractive index is determined as the ratio between the traveled beam paths when the liquid is deposited versus a reference without the liquid sample. Additionally, a mathematical analysis of the geometrical case is included. The theoretical data from our sensor are in good agreement with the experimental results. The resolution achieved by the sensor is better than 10−3 RIU.